Policies affecting changes in ownership of livestock and use of feed resources in the highlands of northern Ethiopia - Benin, Samuel; Ehui, Simeon K.; Pender, J.L. (Oxford University Press, 2004)
This paper examines the factors contributing to decline in ownership of various types of livestock and availability and quality of grazing lands in the northern Ethiopian highlands since, 1991. It also examines the factors contributing to changes in utilisation of various feed resources. Increase in the extent of drought and population growth have contributed significantly to decline in ownership of livestock and availability and quality of grazing resources. On the other hand, better access to markets and increase in participation in credit and extension programmes have contributed to increases in ownership of livestock and use of feed resources. The results suggest that improving access to markets and extension programmes can enhance the role of livestock in improving food security and reducing poverty in the mixed crop livestock farming systems as exist in the Ethiopian highlands. In addition, easing the pressure on agricultural land by providing non farm opportunities and credit, extension and training in these activities will be important.